2022
DOI: 10.1149/1945-7111/ac5c99
|View full text |Cite
|
Sign up to set email alerts
|

Review—Microstructural Modification in Lithium Garnet Solid-State Electrolytes: Emerging Trends

Abstract: Garnet structured solid electrolytes-based lithium metal batteries are the most attractive high energy density electrochemical energy storage candidates for the transportation and grid sectors. Various studies are carried out to address the concerns of lithium garnets as solid electrolytes and improve their electrochemical performance in lithium metal batteries. Interfacial engineering is a widely studied strategy for improving lithium garnet electrolyte-electrode interfacial contact and critical current densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 106 publications
(177 reference statements)
0
5
0
Order By: Relevance
“…Previous research attempted to solve this problem and found some factors contributing to lithium dendrite growth, such as the low relative density [6], large grain size of LLZO [7], and poor contact between lithium metal and LLZO [8]. Numerous solutions have been developed to address these problems [9]. The relative density of LLZO could reach 98% with a small average grain size (< 5 μm) [10,11] and the interfacial impedance decreases to lower than 1 Ω•cm 2 [6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research attempted to solve this problem and found some factors contributing to lithium dendrite growth, such as the low relative density [6], large grain size of LLZO [7], and poor contact between lithium metal and LLZO [8]. Numerous solutions have been developed to address these problems [9]. The relative density of LLZO could reach 98% with a small average grain size (< 5 μm) [10,11] and the interfacial impedance decreases to lower than 1 Ω•cm 2 [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the application of metallic lithium anode with liquid electrolyte results in unsafe and performance-sapping lithium dendrite growth during cycling. , To circumvent these issues, solid-state lithium batteries (SSLBs) are regarded as one of the most favorable approaches. A solid electrolyte is a major component of SSLBs and the rigid nature of these electrolyte systems theoretically prevents lithium dendrite propagation and provides improved safety. …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, solid electrolytes allow the use of lithium-metal anode with the highest theoretical capacity (3860 mA h g −1 ) that leads to ASSLBs with high energy density. 12–15…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, solid electrolytes allow the use of lithium-metal anode with the highest theoretical capacity (3860 mA h g −1 ) that leads to ASSLBs with high energy density. [12][13][14][15] Inorganic solid electrolytes that are the main focus of recent research are sodium superionic conductors (NASICON Li 1.3 -Al 0.3 Ti 1.7 (PO 4 ) 3 or LATP), perovskites (Li 0.5 La 0.5 TiO 3 or LLTO), lithium superionic conductors (LISICON Li 14 ZnGe 4 O 16 ), lithium phosphorous oxynitride (LiPON), lithium garnets (Li 7 -La 3 Zr 2 O 12 , LLZO), and sulde (L 7 P 3 S 11 ) materials. [16][17][18][19][20][21] Among them, lithium-stuffed garnet solid electrolytes, Li 7 -La 3 Zr 2 O 12 (LLZO), are appealing choices for use in ASSLBs because of several reasons, including high lithium ion conductivity in ambient atmosphere, good stability against metallic lithium anode and wide electrochemical potential windows.…”
Section: Introductionmentioning
confidence: 99%